Masculinity and mass violence in Africa: Ongoing debates, concepts and trends - Rose Løvgren (Danish Institute for International Studies (DIIS), 2015)
Attention to the role of masculinity in mass violence on the African continent seems to have been rising in recent years. The gender identities of men as perpetrators, recruitment pools, and victims of violence are subjects of increasing discussion within academia and policy making. This working paper sketches out ongoing debates, concepts and trends within the literature that engages masculinity and the concept's relation to war, conflict and genocide in various African countries. Highlighting implicit assumptions about gendered hierarchy and difference, as well as their imperial and colonial legacies, the working paper draws up analytical tendencies in how African masculinities have been constructed within interpretations of violence. Rather than provide answers to how masculinities should be understood, the paper focuses on critically inquiring into the political implications of various existing conceptualizations and policies concerning the gendered dynamics of mass violence.
Keywords: 330